Immigration and housing rents in American cities - Albert Saiz (Institute for the Study of Labor (IZA), 2006)
Is there a local economic impact of immigration? Immigration pushes up rents and housing values in US destination cities. The positive association of rent growth and immigrant inflows is pervasive in time series for all metropolitan areas. I use instrumental variables based on a shift-share of national levels of immigration into metropolitan areas. An immigration inflow equal to 1% of a city's population is associated with increases in average rents and housing values of about 1%. The results suggest an economic impact that is an order of magnitude bigger than that found in labor markets.
Keywords: J61; R23; R31; 330; immigration; housing prices; Einwanderung; Miete; Wohnungsmarkt; Immobilienpreis; Großstadt; USA